Deposition and Characterization of Cobalt doped Titanium Dioxide Thin Films using Sol-gel Method - Abu Mansor, M. Luqman Harith; Hussin, Rosniza; Kamdi, Zakiah; Ainuddin, Ainun Rahmahwati; Ibrahim, Siti Aida; Mohamed Hatta, Mohamed Nasrul; Yunos, Muhamad Zaini (Journal of Science and Technology, 2018)
Thin films become more importance and a lot of research and studies have been done toward the improvement and achievement. In this study, the new finding of deposition Cobalt (Co) doped TiO2 thin films have been prepared by sol-gel method onto a glass substrate at room temperature for enhancement of optical properties. The effect of Co doped TiO2 thin films have been studies. The different concentration of Co was varied from 1 wt %, 2 wt % and 3 wt % dopant. The deposition of Co doped TiO2 was prepared by using sol-gel method and spin coating technique on the glass substrate. The obtained films have been annealed at 400 oC, 500 oC, and 600 oC for 2 hours and were investigated. X-ray diffraction (XRD) peaks revealed that the films exhibit showed that Co:TiO2 films are anatase crystalline structure at orientation (101). The surface morphologies of the Co:TiO2 thin films were evaluated by Field Emission Scanning Electron Microscopy (FESEM) and Atomic Force Microscopy (AFM). The calcination temperature and content of Co dopant gave a different size of particle and grain boundary. Root Mean Squared (RMS) roughness values increase by increasing the molar ratio of dopant. While, as the calcination temperature increases, the RMS also increasing. The optical properties were studied by using UV-visible spectroscopy (UV-Vis) with a wavelength range of 300 nm to 1000 nm. The calculated optical band gap decreases with increasing of Co doping.